Meminimalkan Tax Stamp Waste dan Claimable Waste pada Departemen Secondary Processing PT. X dengan menggunakan DMAIC - Natasah Bunardi; I Gede Agus Widyadana (Jurnal Titra, 2018)
PT. X is a company engaged in the cigarette industry in Indonesia. This research was conducted at PT. X and focuses on the Secondary Processing department. Secondary Processing Department produces cigaretterod to become a shipping case. During the process, Secondary Processing Department always produces tax stamp waste and claimable waste, and sometimes this waste exceeds the target company. Improvements need to be done within this company so that the tax stamp waste and claimable waste can be reduced and not exceed the target. The improvement and data processing used in this research is using DMAIC. DMAIC assists this research by finding the root cause and making improvements to the root causes that have been discovered. The tool used to assist in finding the root of the problem is fish bone diagram. The fish bone diagram helps this research in order to fix the problem down to its roots so that the possibility of such problems may occur again are smaller. The result of all improvements that already done can reduce tax stamp waste and claimable waste to be below the target.